Abiu – An emerging potential fruit for diversification in fruit orchard - Karunakaran, G; Rupa, T R; Arivalagan, M; Tripathi, P C; Sakthivel, T; Ruchitha, T; Abhilash, K (Indian Horticulture, 2024)
Pouteria caimito (Ruiz & Pavon.) Radlk. is commonly known as abiu, yellow star apple, yellow sapote and caimo etc., is an excellent and rare fruit of Sapotaceae family. This exotic fruit is delicious and nutritious that has drawn much attention not only because of its attractive bright golden yellow colour but also due to ease of cultivation. Abiu fruits are mostly preferred as table fruit and also being used in processing industry. This article discusses about the importance, nutritive value and strategies to diversify abiu in fruit orchard.